(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The global pandemic COVID-19 gave a big impact worldwide either in terms of the medical condition, economy, education, or working mode. Millions of deaths were reported due to COVID-19. At the moment, a central repository to store all information about the patient is very significant for monitoring and analysis purposes. Hence, this paper presents a preliminary study on human temperature screening during COVID-19 and the effect of warm and hot weather on body temperature with COVID-19 transmission. The information was stored in a dashboard and the effect of warm and hot weather on body temperature was further analyzed by using the Spearman Rank Correlation Coefficient. Based on the analysis, it showed that the correlation result between cases and all-weather factors has a weak positive correlation and weak negative correlation. In the future, more dataset and external factors should be further integrated for a better result.